Socioeconomic Status and Satisfaction with Public Healthcare System in Iran - Najmeh Maharlouei; Mojtaba Akbari; Maryam Akbari; Kamran B. Lankarani (Shiraz University of Medical Sciences, 2017)
Background: The users' satisfaction is a method for evaluating the efficacy of healthcare system. We aimed to evaluate the association between the users' socioeconomic status (SES) and satisfaction with the healthcare system in Shiraz, Iran. Methods: This cross-sectional study was conducted from December, 2013 to March, 2014, in Shiraz, Iran. 3400 households were recruited by multi-stage cluster random sampling. Information about demographic, insurance status, and users' satisfaction was derived from face-to-face interviews. Satisfaction with healthcare system was assessed by using 5-point Likert scale statements, which ranged from "very dissatisfied" to "very satisfied". All statistical analyses were performed using SPSS-21. Results: Overall, 1.6% (55) of the respondents were very satisfied, while 6% (203) were very dissatisfied with healthcare system. Participants were classified into high SES (26.3%), middle SES (47.9%) and low SES (25.8%). It was discovered that the better the SES, the more frequent were the respondents dissatisfied with healthcare system (P<0.001). Also, dissatisfied respondents were significantly older (P=0.036). Moreover, women were more dissatisfied with healthcare system (P=0.005). Also, dissatisfied respondents had significantly a higher level of education than satisfied ones (P<0.001). Furthermore, logistic regression revealed that age (P=0.04), marital status (P=0.01), insurance status (P<0.001), SES (P<0.001), and having supplemental insurance (P=0.02) were determinant factors of satisfaction with healthcare system. Conclusion: This study demonstrated that users' sex, age, educational level, and SES were related to dissatisfaction with healthcare system. Meanwhile, clients' age, SES, insurance status and marital status were recognized as determinant factors.